Sistem Pakar Diganosa Jenis Kecanduan Narkoba Menggunakan Teorema Bayes - Iqbal Adji Setiadhi (Journal of Information System and Artificial Intelligence, 2021)
This research was to design an expert system to diagnose types of drug addiction using Bayes’ Theorem. Bayes' Theorem is a theorem used in statistics to calculate the probability of a hypothesis. The basis of the expert system knowledge is obtained from the acquisition of doctors’ knowledge. This study used 32 data of medical records. The medical records were incorporated into the system. The results of the system were matched with the experts to get the maximum matching number and a close identification result. Based on the 32 data tested against the experts and the system, the system could detect 4 types of drugs, namely Cannabis, Cocaine, Opioids, and Hallucinogens. There were 27 patients who were addicted to marijuana and they matched the experts’ validation, meanwhile 5 patients did not match the experts’ validation. The accuracy level of the system based on the results of the experts’ validation and the system was 84.38%.